2021
DOI: 10.3390/nano11040849
|View full text |Cite
|
Sign up to set email alerts
|

Origin of Magnetism in γ-FeSi2/Si(111) Nanostructures

Abstract: Magnetism has recently been observed in nominally nonmagnetic iron disilicide in the form of epitaxial γ-FeSi2 nanostructures on Si(111) substrate. To explore the origin of the magnetism in γ-FeSi2/Si(111) nanostructures, we performed a systematic first-principles study based on density functional theory. Several possible factors, such as epitaxial strain, free surface, interface, and edge, were examined. The calculations show that among these factors, only the edge can lead to the magnetism in γ-FeSi2/Si(111)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
4
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 36 publications
0
4
0
Order By: Relevance
“…In other words, there is a preferential distribution of iron atoms deep into the NRs. The distribution “in-plane” is associated with iron atoms near the steps and kinks, as theoretically proven [ 8 ]. Taking into account the coagulation of the islands in our case, some of the iron atoms are highly probable to diffuse to the substrate and can be distributed over the thickness of the NRs, and some other propagate along their surface, as reported in [ 2 ].…”
Section: Discussionmentioning
confidence: 92%
See 2 more Smart Citations
“…In other words, there is a preferential distribution of iron atoms deep into the NRs. The distribution “in-plane” is associated with iron atoms near the steps and kinks, as theoretically proven [ 8 ]. Taking into account the coagulation of the islands in our case, some of the iron atoms are highly probable to diffuse to the substrate and can be distributed over the thickness of the NRs, and some other propagate along their surface, as reported in [ 2 ].…”
Section: Discussionmentioning
confidence: 92%
“…The issue of induced magnetism in nanostructures (NSs) of non-magnetic materials such as iron mono (FeSi) and disilicides (FeSi 2 ) has attracted much attention from experimenters [ 1 , 2 , 3 , 4 , 5 , 6 ] and theorists [ 7 , 8 , 9 , 10 ]. The appearance of ferromagnetism (FM) and superparamagnetism (SPM) in NSs from a theoretical point of view can be explained either by a change in a number of first neighbors and interatomic distances of iron atoms in the bulk crystal structure [ 7 ] or by the presence of Fe atoms at the edges of the NS, which have nonzero spin moments and are a source of magnetism [ 8 ]. In ultrathin films of FeSi, as theoretically established in [ 9 ], FM is determined by the upper layer in the FeSi structure (i.e., by termination).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The study of these materials is a significant feature that provides an indication of the technological development. Fe-A (Ni, Co and Si) alloys have a range of magnetic properties that make them useful for various applications, including high magnetic permeability, high magnetization saturation, and low coercivity field [1][2][3]. These materials are applied in different areas, for example, magnetic application, biomedical application, and Turbomachinery components [4][5][6].…”
Section: Introductionmentioning
confidence: 99%
“…Liang et al has demonstrated transformation of s → β nanowires on Si(110) by annealing at 800 °C [ 33 ]. Geng et al [ 34 ], using a first principle study based on density functional theory, have explored the effects of epitaxial strain, free surface, interface and edges of grown nanoislands on the resulting magnetic properties, and concluded that only the edges constituted a sizable contribution to the magnetism of γ-FeSi 2 /Si(111) system. By assigning bulk CaF 2 structure to the γ-FeSi 2 NSs, their research studied the implicitly combined intrinsic (composition and crystal and electronic structure) and extrinsic (island boundaries) factors.…”
Section: Introductionmentioning
confidence: 99%